2020
DOI: 10.1093/ofid/ofaa290
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Platform Demonstrates High Adherence in Patients Receiving Fixed-Dose Ledipasvir and Sofosbuvir: A Pilot Study

Abstract: This study evaluated health outcomes among people who inject drugs infected with hepatitis C virus using an artificial intelligence platform. Mean (SD) cumulative adherence (visual confirmation of administration) was 91.3% (SD=10.5%). Most subjects (88.2%) achieved ≥ 80% adherence to treatment and 88.2% (15 of 17) achieved a sustained virologic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Mean cumulative adherence in the AIP studies were 91.3% 45 and 96.2%, 47 respectively. These are relatively higher than the adherence measured by blister packs in the 51 participants in the DOT arm of the PREVAIL study (86%) 33 and that of the SIT arm (75%).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Mean cumulative adherence in the AIP studies were 91.3% 45 and 96.2%, 47 respectively. These are relatively higher than the adherence measured by blister packs in the 51 participants in the DOT arm of the PREVAIL study (86%) 33 and that of the SIT arm (75%).…”
Section: Discussionmentioning
confidence: 94%
“…The first was an open-label, non-randomized study of 17 PWID during self-administration of LDV/SOF for 8 ( n = 2) or 12 weeks ( n = 15). 45 All participants completed treatment and mean cumulative adherence by visual AIP was 91.3%. Fifteen of 17 participants (88.2%) achieved SVR12.…”
Section: Artificial Intelligence Platformsmentioning
confidence: 98%
See 1 more Smart Citation
“…The vDOT could bridge this gap where more objective adherence monitoring approaches are desired in persons where adherence is of concern. In line with this, artificial intelligence-based mobile adherence monitoring platforms have also been piloted [ 33 ], including a study in 17 PWID that showed mean DAA adherence rates of 91% [ 34 ]. Collectively, several adherence monitoring tools have been used with success in PWUD, and our findings provide support for vDOT and WOT as additional tools that can be used in this population.…”
Section: Discussionmentioning
confidence: 99%
“…Infographics or interactive visualizations using pictures and illustrations have been effective for complex information communication and have proven the age-old saying "a picture is worth a thousand words" [22][23][24][25]. Furthermore, AI-based smartphone devices have proven to be effective in clinical trials and chronic disease management to improve medication adherence [21,26]. Utilizing advanced machine learning algorithms, smartphone apps have the potential to improve medication information delivery to patients.…”
Section: Introductionmentioning
confidence: 99%